Strategi Implementasi Teknologi Digital dalam Meningkatkan Pemasaran Produk pada UKM Mesak - Melda Agnes Manuhutu; Dewi Dewi; Yoland Yoland; Paulinus Paulinus; Yulven Yulven; Natasya Leuwol (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The Mesak SME is a micro-enterprise in the food sector that still relies on conventional marketing strategies. This reliance on traditional promotional methods has prevented it from optimally reaching the digital market. However, utilizing digital technology is currently a crucial aspect of business development, particularly for increasing competitiveness and expanding market reach. Therefore, this community service activity was carried out with the primary goal of improving the Mesak SME's capacity to adopt digital marketing strategies. The community service program was designed in a structured and sustainable manner through several stages: an initial survey to determine the SME's existing condition, observation of existing marketing activities, and socialization of the benefits of digital technology in business development. Next, intensive training was conducted, covering the use of social media as a promotional tool, creating engaging digital content that aligns with the product's characteristics, and introducing e-commerce platforms to expand market access. The training focused on a practical approach that is easy for SMEs to understand. Furthermore, mentoring and evaluation were provided to ensure the sustainability of the digital strategy implementation after the program was completed. Through this series of activities, it is hoped that the Mesak SME will be able to actively utilize social media, produce engaging content, and market its products through various digital channels. The results of this activity are not only aimed at increasing sales volume but also at building a more professional and competitive business image, both in local and digital markets. With improved digital marketing capabilities, Mesak SMEs are expected to develop independently and sustainably in the era of digital transformation.